Buku Panduan Perpustakaan Universiti Sains Malaysia (Guidebook Universiti Sains Malaysia Library) 2018 - Perpustakaan, Hamzah Sendut (Perpustakaan Hamzah Sendut, 2018)
The Universiti Sains Malaysia Library was established in 1969. Initially, the Library operated in borrowed premises at the Malayan Teacher’s Training College, Gelugor. When USM moved to its own permanent campus at Minden in 1971, the Library was housed in a heritage building which is now the Muzium dan Galeri Tuanku Fauziah.